1985
DOI: 10.1037/0022-006x.53.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive bias and depression in psychiatrically disturbed children and adolescents.

Abstract: The relation between cognitive distortion and depression, found in adult affective disorders, has not previously been demonstrated in childhood affective disorders. Therefore, a Cognitive Bias Questionnaire for Children (CBQC) was developed to examine this relation in a sample of 39 psychiatrically disturbed children and adolescents. The depressed-distorted (DD) scale from the CBQC was significantly correlated with psychiatric and self-reported ratings of depression and could significantly discriminate affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 7 publications
4
54
0
2
Order By: Relevance
“…Less clear, however, is the CDI's ability to distinguish between children with depressive disorders and children who display other kinds of clinical problems [for a review, see Silverman and Rabian, 1999]. Some studies have found that children with depressive disorders score significantly higher on the CDI than nondepressed clinical samples [e.g., Haley et al, 1985;Hodges, 1990;McCauley et al, 1988; whereas other studies have reported no differences between the CDI scores of depressed and nondepressed clinical samples [e.g., Kazdin, 1987;Kazdin et al, 1983;Saylor et al, 1984].…”
mentioning
confidence: 97%
“…Less clear, however, is the CDI's ability to distinguish between children with depressive disorders and children who display other kinds of clinical problems [for a review, see Silverman and Rabian, 1999]. Some studies have found that children with depressive disorders score significantly higher on the CDI than nondepressed clinical samples [e.g., Haley et al, 1985;Hodges, 1990;McCauley et al, 1988; whereas other studies have reported no differences between the CDI scores of depressed and nondepressed clinical samples [e.g., Kazdin, 1987;Kazdin et al, 1983;Saylor et al, 1984].…”
mentioning
confidence: 97%
“…Beck's theory has prompted research for testing whether children with depressive symptomatology engage in distorted patterns of thinking. Some of these studies have used measures that ask children about hypothetical situations to determine if their thinking reflects distorted processing of information (e.g., Children's Negative Cognitive Error Questionnaire [CNCEQ], Leitenberg, Yost, & Carroll-Wilson, 1986; Cognitive Bias Questionnaire for Children [CBQC], Haley, Fine, Marriage, Moretti, & Freeman, 1985). Other studies have used more objective indicators of children's circumstances, in addition to subjective reports, to demonstrate that depressed children distort information about themselves (e.g., Asarnow, Carlson, & Guthrie, 1987;Kendall, Stark, & Adam, 1990;McGee, Anderson, Williams, & Silva, 1986;Meyer, Dyck, & Petrinack, 1989).…”
Section: Negative Self-perceptionsmentioning
confidence: 99%
“…Rather than relying on questionnaires that ask children about hypothetical situations (e.g., see Haley et al, 1985;Leitenberg et al, 1986), both children's and teachers' ratings of competence were obtained to estimate the accuracy of children's judgments about the self. Although not subject to children's own reporting biases, teacher evaluations are not perfect indicators of children's academic and social performance.…”
Section: Limitationsmentioning
confidence: 99%
“…Estos resultados son acordes con los encontrados por otros autores sobre los errores cognitivos y la sintomatología depresiva (Haley et al, 1985;Kendall, 1990;Leitenberg et al 1986). De hecho, Kendall (1990) encuentra una correlación significativa entre las puntuaciones obtenidas en el CDI y las distorsiones cognitivas (en relación con las percepciones negativas que realiza el sujeto del ambiente, así como la desvaloración no.…”
Section: Discussionunclassified
“…En este sentido, Haley et al (1985) relacionan la presencia de pensamientos distorsionados con los trastornos del estado de ánimo en estas edades y Leitenberg et al (1986) encuentran correlaciones significativas entre los sesgos cognitivos de sobregeneralización y catastrofismo con la depresión en niños y adolescentes.…”
Section: Introductionunclassified